Kepemimpinan Visioner Kepala Sekolah di SMA IT Insan Mulia Boarding School Pringsewu - Septa Putri Nugraha; Hasan Hariri (Jurnal Humaniora dan Ilmu Pendidikan, 2022)
Purpose: This study aims to determine visualizing, showing foresight, and continuous learning of principals at SMA IT Insan Mulia Boarding School Pringsewu. Methodology: The design of this study uses the Human instrument model, descriptive qualitative, case study, with data collection in the form of interviews, observation, and documentation. Results: The Principal of IT Insan Mulia Boarding School Pringsewu High School in compiling the school's vision, mission, and annual program plan is in accordance with visualizing characteristics, the Principal of IT Insan Mulia Boarding School Pringsewu High School in developing human resources, planning work culture, and planning the development of student achievement has in accordance with the characteristics of showing foresight, the Principal in terms of planning HR career development, planning cooperative relations, and planning HR certification programs are in accordance with the characteristics of continuous learning. Limitations: The limitations of this study are that it takes a long time, is difficult to investigate causality, and is not statistically representative. Contribution: This research can contribute to the leadership of educational institutions, both school principals, school management, educational foundations, and can also be applied by teachers in educational institutions.